The Impact of Using Clean Fuel on the Risk of Stunting in Children Aged 0-59 Months - Sakinah Rahma Firdaningtyas; Djoni Hartono (Eduvest - Journal of Universal Studies, 2024)
Stunting is a critical global health challenge, particularly in developing nations, affecting children's physical, cognitive, and socioeconomic outcomes. This study investigates the impact of clean cooking fuel use on stunting risk among children aged 0–59 months in Indonesia, employing cross-sectional data from the 2014 Indonesian Family Life Survey (IFLS) and the Propensity Score Matching (PSM) method. The results reveal that households using clean cooking fuels, such as liquefied petroleum gas (LPG), significantly improve children's Height-for-Age Z-scores, reducing stunting risk. Factors including higher household education, income levels, and access to urban areas positively influence clean fuel adoption. The study underscores the importance of clean energy policies and increased awareness, particularly in rural areas, to mitigate health disparities and improve childhood growth outcomes. These findings contribute to the growing evidence linking clean energy transitions with enhanced public health and child development indicators.